The Dissemination and Molecular Characterization of Clonal Complex 361 (CC361) Methicillin-Resistant Staphylococcus aureus (MRSA) in Kuwait Hospitals - Sarkhoo, Eiman; Udo, Edet E.; Boswihi, Samar S.; Monecke, Stefan; Mueller, Elke; Ehricht, Ralf (Frontiers in Microbiology, 2021)
Methicillin-resistant Staphylococcus aureus (MRSA) belonging to clonal complex 361 (CC361- MRSA) is rare among patients’ populations globally. However, CC361-MRSA has been isolated with an increasing trend among patients in Kuwait hospitals since 2010. This study investigated the molecular characteristics of CC361-MRSA isolated from patients in Kuwait hospitals in 2016-2018 to understand their genetic relatedness and virulence determinants. Of 5223 MRSA isolates investigated by DNA microarray, 182 (3.4%) isolates obtained in 2016 (N=55), 2017 (N=56), and 2018 (N=71) were identified as CC361-MRSA. The CC361-MRSA isolates were analyzed further using antibiogram, spa typing and multi locus sequence typing (MLST). Most of the isolates were resistant to fusidic acid (64.8%), kanamycin (43.4%), erythromycin (36.3%) and clindamycin (14.3%) encoded by fusC and aphA3 respectively. Nine isolates (4.9%) were resistant to linezolid mediated by cfr. The isolates belonged to 22 spa types with t3841 (N=113), t315 (N=16), t1309, (N=14) and t3175 (N=5) constituting 81.3% of the spa types, four genotypes (strain types), CC361-MRSA-[V/VT+fus] (N=112), CC361-MRSA-IV, WA MRSA-29 (N=36), CC361-MRSA-V, WA MRSA-70/110 (N=33) and CC361-MRSA-[V+fus] variant (N=1). MLST conducted on 69 representative isolates yielded two sequence types: ST361 (11/69) and ST672 (58/69). All CC361-MRSA isolates were positive for cap8, agr1, and the enterotoxin egc gene cluster (seg, sei, selm, seln, selo, selu). The tst1 was detected in 19 isolates. The immune evasion cluster (IEC) genes type B (scn, chp, sak) and type E (scn, sak) were detected in 20 and 152 isolates respectively. The CC361-MRSA circulating in Kuwait hospitals consisted of two closely related sequence types, ST361 and ST672 with ST672-MRSA [V/VT +fus] as the dominant genotype. The dissemination of these newly emerged clones and the emergence of linezolid resistance limits therapeutic options, as well as present significant challenges for the control of MRSA infections in Kuwait hospitals.